The carbohydrate switch between pathogenic and immunosuppressive antigen‐specific antibodies. Issue 8 (28th June 2013) - Collin, Mattias; Ehlers, Marc
Abstract: IgG antibodies have one conserved N‐glycosylation site at Asn 297 in each of their constant heavy chain regions. These Fc glycans influence the overall structure and pro‐ or anti‐inflammatory effector functions of IgG antibodies. The biantennary core glycan structure, consisting of four N‐acetyl‐glucosamine (GlcNAc) and three mannose residues, can be further decorated with fucose, a bisecting GlcNAc and terminal galactose or galactose plus sialic acid. Non‐galactosylated (agalactosylated; G0) IgG antibodies have long been associated with pro‐inflammatory effector functions in autoimmune patients with rheumatoid arthritis (RA). In contrast, it has been shown that sialylated IgGs are responsible for anti‐inflammatory effects of intravenous immunoglobulin (IVIG; purified IgG from pooled human plasma), which is administered at high doses (2 g/kg) for the systemic treatment of autoimmune patients. It has become increasingly evident that pro‐inflammatory immune responses, such as autoimmune reactions, primarily induce antigen‐specific G0 IgGs, whereas tolerance induces immunosuppressive galactosylated and sialylated IgGs. Under physiological conditions, differentially glycosylated IgGs mediate their pro‐ or anti‐inflammatory effector functions obviously as immune complexes (IC) in an antigen‐specific manner. Therefore, antigen‐specific galactosylated and sialylated IgGs may be a promising therapeutic tool for re‐establishing tolerance against defined (self‐) antigens in autoimmune or allergic patients. Here, we summarize these findings and outline our viewpoint on the development and function of differentially glycosylated antigen‐specific IgG antibodies.